Effects of Web 2.0 Tools (Kahoot, Quizlet, Google Form Example) on Formative Assessment in Online Chemistry Courses - Sibel Sadi Yılmaz; Mehmed Diyaddin Yaşar (Universitas Pendidikan Indonesia, 2023)
This study aims to examine the effects of using Kahoot, Quizlet, and Google Forms as gamification and formative assessment tools in the Chemistry II course conducted through synchronous online instruction during the COVID-19 period. The study was conducted based on a triangulation design, one of the mixed research designs in which quantitative and qualitative data collection tools and analyses are used together. This study was conducted with 32 volunteer participant students studying in the first grade of the science education department. The study used a Solutions Achievement Test (SAT) and a Chemical Kinetics Achievement Test (CKAT) as quantitative data collection tools. The results of the data analysis in the SAT and CKAT revealed a significant difference in favor of the posttest. The Student Opinion Questionnaire (SOQ), created using Conversational Interviews (CI) held with students throughout the implementation, was used as a qualitative data collection tool. The qualitative data analysis determined that the students did not participate in online classes due to the accessibility of the course video recordings, the absence of a compulsory attendance rule, and restricted access to the internet and technology. The use of Kahoot, Quizlet, and Google Forms in online classes and in students’ free time outside class had positive effects, namely enjoyable and productive lessons, contribution to professional teaching skills, reinforcement of learned knowledge, and students’ awareness of their learning levels through the feedback they received in a stress-free competitive environment. In addition, qualitative data were obtained to show that these applications were more effective in verbal subjects.